Immunophenotype of pediatric‐onset mastocytosis does not correlate with clinical course. Issue 4 (23rd May 2019) - Greenberger, Shoshana; Landov, Hagai; Confino, Yitzhak; Vaknine, Hananya; Avivi, Camila; Baum, Sharon; Barzilai, Aviv
Abstract: Background: Pediatric mastocytosis differs from adult mastocytosis in its presentation and clinical course. However, the data regarding the immunophenotypic characterization of mast cells in children are limited. Our objective was to evaluate the immunophenotype of mast cells in pediatric mastocytosis and correlate it with the clinical course. Methods: Biopsy specimens of children with cutaneous mastocytosis were retrieved from the institutions of pathology and were stained for CD25, CD2, and CD30. The percentage of mast cells and the staining intensity were correlated with the clinical data. Results: Twenty‐five biopsy specimens were included in the study. Patients' average age was 15.4 at presentation and 37.5 months at biopsy performance. Clinical presentations included maculopapular cutaneous mastocytosis in 79% and mastocytoma in 21% of cases. CD25, CD2, and CD30 were positive in 60%, 44%, and 84% of the biopsy specimens, respectively. The staining score was significantly higher for CD30 as compared to those for CD25 and CD2 ( P  = 0.02). No correlation was found between the immunophenotype and the clinical form or course of disease. Conclusions: Our results confirm that CD30 is a sensitive marker for pediatric‐onset mastocytosis. Nevertheless, its expression does not correlate with clinical subtype or clinical course. The sensitivity of CD25 is higher than that of CD2 in skin lesions.